Privacy and Ledger Size Analysis for Healthcare Blockchain - Im, Hyowon; Kim, Ki Hyung; Kim, Jai Hoon (International Conference on Information Networking, 2020)
Since personal health information is sensitive data, it should not be accessible to anyone. Only authorized users should be able to see it. Blockchain, new middleware platform paradigm, can provide confidentiality and data sovereignty as well as transparency and traceability. Personal Health Record (PHR) incorporating blockchain can be managed by the patient themselves, not by the centralized institution, through blockchain. In this paper, PHR based on Hyperledger Fabric (consortium blockchain) is proposed. We also analyze and compare performance in terms of transaction delay and ledger size for private data access.
Keywords: Authorized users; ledger size; Middleware platforms; Personal health informations; Personal health record; Private data; Sensitive datas; Size analysis; blockchain; consortium blockchain; healthcare; hyperledger fabric; ledger size; PHR; privacy